2009
DOI: 10.1038/ismej.2009.87
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the spatial diversity and novel lineages of mycoplankton in Hawaiian coastal waters

Abstract: Microbial community diversity and composition have critical biogeochemical roles in the functioning of marine ecosystems. Large populations of planktonic fungi exist in coastal ocean waters, yet their diversity and role in carbon and nutrient cycling remain largely unknown. Lack of information on critical functional microbial groups limits our understanding of their ecological roles in coastal oceans and hence our understanding of its functioning in the ocean's carbon and nutrient cycles. To address this gap, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
88
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 57 publications
10
88
3
4
Order By: Relevance
“…As with our own study, Gao et al (2008) found a high diversity of Basidiomycete sequences within the Malasseziales, Corticiales, Agaricales and Polyporales. In another study of planktonic marine Coral-associated marine fungi AS Amend et al fungi (Gao et al, 2009), clone libraries were dominated by sequences within the Pucciniomycetes, a group relatively underrepresented here.…”
Section: Discussionmentioning
confidence: 77%
“…As with our own study, Gao et al (2008) found a high diversity of Basidiomycete sequences within the Malasseziales, Corticiales, Agaricales and Polyporales. In another study of planktonic marine Coral-associated marine fungi AS Amend et al fungi (Gao et al, 2009), clone libraries were dominated by sequences within the Pucciniomycetes, a group relatively underrepresented here.…”
Section: Discussionmentioning
confidence: 77%
“…Riverine inputs of fungi to coastal waters may to some extent account for the observations made of the biogeographical distribution of mycoplankton in the Pacific Ocean that have shown that diversity is greater in coastal waters around the Hawaiian Islands compared with the open ocean (Gao et al, 2010;Wang et al, 2014), and that Ascomycota in particular are especially more abundant nearer the coast (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies of marine mycoplankton diversity have been largely based on samples collected from one-off sampling campaigns that have provided important and insightful 'snap shots' of diversity, but with limited temporal resolution (Bass et al, 2007;Gao et al, 2010;Richards et al, 2012;Manohar and Raghukumar, 2013;. Time series assessments of other plankton groups have proven invaluable in developing our understanding of their biology and ecology (Karl and Church, 2014;Fuhrman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, to our knowledge, no detailed investigations of the response of marine yeast communities to experimental confinement exist and estimates on the percentage of culturable marine yeasts are lacking (Fell 2001). Recently, a DGGE analysis of mycoplankton of Hawaiian coastal waters revealed many new fungal phylotypes but not a single match with fungi previously cultured from this environment (Gao et al 2010). Therefore, future studies on ocean acidification effects on marine yeasts should include direct detection methods.…”
Section: Yeast Community At Helgoland Roadsmentioning
confidence: 99%